Single-cell sequencing in ovarian cancer: a new frontier in precision medicine. Issue 1 (February 2019) - Winterhoff, Boris; Talukdar, Shobhana; Chang, Zenas; Wang, Jinhua; Starr, Timothy K.
Abstract : Purpose of review: This article discusses the advances, applications and challenges of using single-cell RNA sequencing data in guiding treatment decisions for ovarian cancer. Recent findings: Genetic heterogeneity is a hallmark of ovarian cancer biology and underlies treatment resistance. Defining the different cell types present within a single ovarian cancer is difficult, but could ultimately lead to improvements in diagnosis and treatment. Next-generation sequencing technologies have rapidly increased our understanding of the molecular landscape of epithelial ovarian cancers, but the majority of these studies are conducted on bulk samples, resulting in data that represents an 'average' of all cells present. Single-cell sequencing provides a means to characterize heterogeneity with a tumor tissue in ovarian cancer patients and opens up opportunity to determine key molecular properties that influence clinical outcomes, including prognosis and treatment response. Summary: Single-cell sequencing provides a powerful tool in improving our understanding of tumor cell heterogeneity for the purpose of informing personalized cancer treatment.